Perspektif Tafsir Al-Mishbah tentang Membangun Kesadaran untuk Kembali pada Allah Swt - Muhammad Syahrul Mubarak (STAIN Majene, 2023)
This paper is a literature study that talks about the message of self-awareness to return to Allah Swt. The intended return is divided into two things, the first is returning in an active sense through repentance. Repentance also has three meanings, renewing faith, replacing ugliness with good and eliminating sins. Second, returning in a passive sense, namely when a person's life has been revoked (through death). The responsibility for the life of the world will certainly be passed by every human being and plenary happiness is to gain the pleasure of Divine which is proven when returning to Allah Swt a servant succeeds in obtaining and being placed in Allah's heaven. Keywords: Return to Allah, Repentance, Heaven of Allah Swt.